Pengaruh Literasi Keuangan Dan Financial Technology Terhadap Kepuasan Keuangan Ditinjau Dalam Perspektif Ekonomi Islam - Istiqomah, Istiqomah; Saefurrahman, Ghina Ulfa; Eliza, Any (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2025)
Millennials are active users of financial technology (fintech), which helps them manage their finances better. Financial applications and investment platforms make it easy to manage budgets and make investments. However, many millennials also have difficulty understanding basic financial concepts, such as debt management, investment, and retirement planning. This study aims to determine the effect of Financial Literacy and Financial Technology on Financial Satisfaction of the Millennial Generation in Bandar Lampung with several problem formulations, namely; can financial literacy affect financial satisfaction in the millennial generation in Bandar Lampung; can financial technology affect financial satisfaction in the millennial generation in Bandar Lampung; can financial literacy and financial technology affect financial satisfaction in the millennial generation in Bandar Lampung; and how financial literacy and financial technology increase financial satisfaction from an Islamic economic perspective. This type of research is quantitative descriptive using a quantitative approach. The number of samples is 100 respondents determined by the Slovin formula. The data analysis method uses IBM Statistics SPSs 26. The data analysis tests used are descriptive statistical tests, validity and reliability tests, classical assumption tests, t-tests and f-tests, and determination coefficient tests. The results of this study indicate that Financial Literacy does not have a positive and significant effect on financial satisfaction, Financial Technology has a positive and significant effect on financial satisfaction, and financial literacy and financial technology have a simultaneous and significant effect on financial satisfaction.